The Permutable k-means for the Bi-Partial Criterion - Dvoenko, Serge D.; Owsinski, Jan W (Informatica, 2019)
The here applied objective function for clustering consists of two parts, where the first one takes into account intra-cluster relations, and the second – inter-cluster ones. In the case of k-means algorithm, such bi-partial objective function combines cluster dispersions with inter-cluster similarity, to be jointly minimized. The first part only of such objective function provides the “standard” quality of clustering based on distances between objects (the well-known classical k-means). To improve the clustering quality based on the bi-partial objective function, we need to develop the permutable version of k-means algorithm. This paper shows the permutable k-means that appears to be a new type of clustering procedure.